Connecting the dots: the role and potential of portfolios in lifelong teacher development in Italy - Maria Chiara Pettenati (Je-LKS: Journal of E-Learning and Knowledge Society)
Lifelong learning is a cornerstone of teacher professionalism, enabling educators to navigate the complexities of a rapidly evolving educational landscape. This article explores how research and literature address the potential of portfolios, particularly e-portfolios, as dynamic tools to promote reflective practice, professional growth, and skill development along the continuum of teacher education: initial teacher training (ITE), induction, and continuing professional development (CPD). This paper examines the roles of portfolios, particularly e-portfolios, as tools for fostering reflective practice, professional growth, and the development of competencies across the continuum of teacher education: initial teacher education (ITE), induction, and continuous professional development (CPD). Drawing on established models and recent educational reforms, this position paper examines several critical dimensions that shape the effective implementation of portfolios. Using the Italian education system as a case study, the paper explores how recent reforms and prior experiences can be leveraged to enhance the integration of lifelong portfolios, ensuring continuity and coherence throughout teachers' professional trajectories. Emphasis is placed on the importance of aligning portfolio practices with professional standards, establishing robust training programs, and developing supportive cultural and technological infrastructures. By addressing the opportunities and challenges of embedding portfolios in teacher education, this research contributes to the broader discourse on fostering systemic approaches to professional development and improving the quality of education.